2018
DOI: 10.1088/1741-4326/aaad78
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the formation of the scrape-off layer density shoulder in JET ITER-like wall L-mode and H-mode plasmas

Abstract: The low temperature boundary layer plasma (Scrape-Off-Layer or SOL) between the hot core and the surrounding vessel determines the level of power-loading, erosion and implantation of material surfaces, and thus the viability of tokamak-based fusion as an energy source. This study explores mechanisms affecting the formation of flattened density profiles, socalled Ôdensity shouldersÕ, in the low-field side (LFS) SOL, which modify ion and neutral fluxes to surfaces Ð and subsequent erosion. We find that increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
57
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(72 citation statements)
references
References 70 publications
9
57
0
Order By: Relevance
“…During the fuelling ramp the divertor moves into a high recycling regime and D α and D γ radiation move towards the low field side (LFS) region, initially in the private flux region (PFR) and then in the main SOL moving upstream once the target density rolls over. This strongly resembles the observation on JET in the Horizontal Target [38]: in this configuration indeed JET upstream profile develops a clear shoulder whenever fuelling is raised, and this is accompanied by a clear D α radiation front moving into the main LFS SOL. On the other hand whenever run in the Vertical Target configuration no shoulder is observed in JET at the same level of fuelling, and D α radiation was confined to a narrow region along the divertor leg.…”
Section: It Is An Iterative Techniquesupporting
confidence: 83%
See 3 more Smart Citations
“…During the fuelling ramp the divertor moves into a high recycling regime and D α and D γ radiation move towards the low field side (LFS) region, initially in the private flux region (PFR) and then in the main SOL moving upstream once the target density rolls over. This strongly resembles the observation on JET in the Horizontal Target [38]: in this configuration indeed JET upstream profile develops a clear shoulder whenever fuelling is raised, and this is accompanied by a clear D α radiation front moving into the main LFS SOL. On the other hand whenever run in the Vertical Target configuration no shoulder is observed in JET at the same level of fuelling, and D α radiation was confined to a narrow region along the divertor leg.…”
Section: It Is An Iterative Techniquesupporting
confidence: 83%
“…On TCV this is true only for the two lower current levels explored in the constant toroidal field scan. Furthermore, in analogy with JET, upstream profile starts evolving with the transition to a high recycling regime for AUG, and is associated with an enhancement of D α radiation in the LFS SOL region, as reported in [38] for JET Horizontal Target plasmas. On the other hand TCV, with its completely open divertor, exhibits a different divertor dynamical behaviour, with the target density increasing almost linearly with fuelling: for both the devices we have proved that the evolution of the upstream profiles follows the dynamics of the divertor, with more pronounced and flatter profiles obtained after target density roll-over.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Indeed in the inertial regime, velocity scales as the square root of blob size δ b , v r ∼ √ δ b and larger blobs with larger velocity has been advocated as the cause of increasing convective radial transport in the higher density regime. More recent results from JET [19] revealed that the shoulder tends to disappear whenever the strike point is moved from the horizontal to the vertical target and that nitrogen seeded discharges exhibit a flatter profile only at very large values of Λ div , defined as the parameter Λ introduced in Equation (1) computed with the typical values at the separatrix, in the mentioned case close to the separatrix. Furthermore the development of a SOL density shoulder has been observed to strongly depend on the plasma current I p [5,20,21]: flat profiles observed at certain levels of the core average density disappear whenever the plasma current is increased.…”
Section: Introductionmentioning
confidence: 99%